Effect of cycling experience and pedal cadence on the near-infrared spectroscopy parameters - Takaishi, T.; Ishida, K.; Katayama, K.; Yamazaki, K.; Yamamoto, T.; Moritani, T. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE Previously we demonstrated that the method to reorder near-infrared spectroscopy (NIRS) parameters against crank angle could serve as a useful measure in providing circulatory dynamics and metabolic changes in a working muscle during pedaling exercise. To examine further applicability of this method, we investigated the effects of cycling experience and pedal cadence on the NIRS parameters. METHODS Noncyclists (NON), triathletes (TRI), and cyclists (CYC) performed pedaling exercises at a work intensity of 75% [OV0312]O while changing pedal cadence (50, 75, 85, and 95 rpm). Physiological and biomechanical responses and NIRS parameters were measured.(2max) RESULTS NIRS measurements determined with the reordered NIRS change demonstrated significant differences depending on the factors. The bottom peak of reordered NIRS changes in muscle blood volume and oxygenation level shifted upward with an increase in pedal cadence in NON but remained unchanged in CYC. The reordered NIRS change demonstrated a temporary increase at the crank angle corresponding to the relaxation phase of the working muscle. This temporary increase was observed even in the highest pedal cadence in CYC. The difference in levels between the peak of the temporary increase and the bottom peak of reordered NIRS change (LPB-diff) for CYC at 85 rpm was significantly larger than that for NON. The results with NIRS parameters corresponded to changes in pedal force and myoelectric activity during pedal thrust. CONCLUSIONS The bottom peak level of the reordered NIRS changes and LPB-diff determined for blood volume are available to detect noninvasively the differences in circulatory dynamics and metabolic change during pedaling exercises performed at different pedal cadences and also to estimate the difference of physiological and technical developments for endurance cycling in athletes.